Islamic Logotherapy Tree: Peta Jalan Menuju Hidup yang Bermakna di Era Kontemporer - Yurika, Rara Eka; Pratiwi, Restika Cahya (Program Studi Bimbingan dan Konseling Islam (BKI) Fakultas Ushuluddin, Adab dan Dakwah (FUAD) Institut Agama Islam Negeri (IAIN), 2024)
Logotherapy, developed by Viktor Frankl, is a psychotherapeutic approach that focuses on the search for the meaning of life as central to the process of healing and mental well-being. The need for an approach that integrates spiritual and cultural values is increasing in the contemporary era. Islam-based logotherapy offers an approach that blends logotherapy principles with Islamic values and teachings, which provides a strong spiritual foundation for individuals in their search for the meaning of life. This approach emphasizes the importance of faith, hope and love as sources of strength in facing life's challenges. Through this integration, Islam-based logotherapy can provide a relevant and effective alternative in the context of an increasingly pluralistic and complex modern society. This research aims to explore the concept and application of Islam-based logotherapy and its benefits in supporting the mental and spiritual health of individuals in the contemporary era. The method used in this research is literature review. The results showed that this approach can enhance psychological well-being by connecting individuals to spiritual values and a greater purpose in life, as well as building resilience in the face of the pressures of modern life. The result of this research is a finding of the Islamic Logotherapy Tree concept scheme which is a theoretical contribution to the stages in implementing logotherapy integrated with Islamic values and organized based on a tree scheme.